THE VALIDITY OF PROBLEM-BASED LEARNING TEACHING MATERIAL FOR TEACHING BASIC STATISTICS TO GRAPHICS ENGINEERING STUDENTS: VALIDITAS BAHAN AJAR BERBASIS PROBLEM-BASED LEARNING UNTUK PEMBELAJARAN STATISTIKA DASAR BAGI MAHASISWA TEKNIK GRAFIS - Fitriani Halik; Lukytta Gusti Acfira; Besse Irna Tawaddud (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This research aims to determine the validity of the problem-based learning module teaching materials in the basic statistics course for graphic engineering students at the State Polytechnic of Creative Media PSDKU Makassar. The type of research used is research and development concerning the 4D development model. The 4D development model consists of several phases: define, design, develop, and disseminate. The product developed is module teaching materials based on problem-based learning on basic statistics material. The test subjects in this research were graphic engineering students at the State Polytechnic of Creative Media PSDKU Makassar. The instrument used in this research was a validation sheet consisting of two validators from design experts and material experts. Based on the results of the research that has been carried out, it is obtained that the analysis of the validation results: (1) the feasibility of the graphic, namely 4.8 is in the very valid category, (2) the feasibility of the language, which is 4.8, is in the very valid category, (3) the feasibility of the content is 4.8 in the very valid category, and (4) the feasibility of presenting that is 4.8, is in the very valid category so that the average value of all aspects is 4.7 which is in the very valid category. So, the problem-based learning module teaching materials in basic statistics courses that have been developed are valid to be used as teaching materials in the learning process.